2019
DOI: 10.1002/ejoc.201900945
|View full text |Cite
|
Sign up to set email alerts
|

Building Up Quaternary Stereocenters Through Biocatalyzed Direct Insertion of Carbon Nucleophiles on Ketones

Abstract: Quaternary stereocenters are privileged structural motifs, widely distributed in natural products and in pharmaceutically active compounds. Asymmetric methods for the efficient construction of these prominent frameworks are rapidly increasing. Biocatalysis represents an alternative to the existing methods of using hazardous metals and chemicals. Enzymes discussed in this mini-review involve thiamine-bisphosphate (ThDP)-dependent lyases, aldolases and hydroxynitrile lyases.[a] 7616 of CO 2 is transferred to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In addition to forming cyanohydrins, HNLs can catalyze the enantioselective addition of nitroalkanes and aldehydes to generate nitro alcohols ( Yuryev et al, 2010 ). Both cyanohydrins and nitro alcohols can be used to construct useful compounds ( Gaggero, 2019 ). For example, nitro alcohols can be converted to 1,2-amino alcohols, conjugated nitroalkenes, α-hydroxy carbonyl compounds, and nitro carbonyl compounds ( Figure 3 ) ( Milner et al, 2012 ).…”
Section: Hydroxynitrile Lyasesmentioning
confidence: 99%
“…In addition to forming cyanohydrins, HNLs can catalyze the enantioselective addition of nitroalkanes and aldehydes to generate nitro alcohols ( Yuryev et al, 2010 ). Both cyanohydrins and nitro alcohols can be used to construct useful compounds ( Gaggero, 2019 ). For example, nitro alcohols can be converted to 1,2-amino alcohols, conjugated nitroalkenes, α-hydroxy carbonyl compounds, and nitro carbonyl compounds ( Figure 3 ) ( Milner et al, 2012 ).…”
Section: Hydroxynitrile Lyasesmentioning
confidence: 99%
“…The produced tertiary alcohols are a widespread motif in bioactive compounds [ 31 ]. Since conventional organic synthesis uses hazardous metals and chemicals biocatalytic alternatives were developed such as the use of thiamine-dependent lyases and hydroxynitrile lyases to furnish 2-alkyl-2-hydroxy ketones, 2-alkyl-2-hydroxy-3-diketones, 3-hydroxy ketones, and ketone cyanohydrins [ 32 ]. Recent successful efforts used dihydroxyacetone phosphate-dependent class II aldolases furnished tertiary alcohol moieties in branched-chain sugars in an enantioselective fashion [ 33 ].…”
Section: Ketones As Alternative Electrophiles For Pyruvic Acid Analogsmentioning
confidence: 99%
“…KphMT E.coli wild type and variants also are suitable for the unprecedented construction of quaternary carbon centers [ 32 , 40 ]. It turns out that ramifications at the 3-positions within the nucleophile present already in the natural oxopantoate pathway were also tolerated in case KphMT E.coli acts in an aldolase fashion.…”
Section: The Extension Of the Aliphatic Chain Length Of The Nucleophilic 2-oxoacidsmentioning
confidence: 99%
“…Thiamine diphosphate (ThDP)-dependent enzymes catalyze C–C bond ligation and cleavage reactions, including pyruvate decarboxylase (PDC), benzoylformate decarboxylase (BFD), benzaldehyde lyase (BAL), transketolase (TK), and so on. In the previous studies, the α-hydroxymethyl ketones have been prepared by direct hydroxymethylation of aldehydes with formaldehyde using BAL and other enzymes through C–C bond formation. ,,,, However, it has been observed that the homocoupling of aldehyde is competing with the hydroxymethylation to give the acyloin byproduct in the BAL-catalyzed reactions. Cosolvents such as 2-methyltetrahydrofuran and large excess of formaldehyde have been used to reduce the homocoupling product, but the reaction still must be carried out at low substrate concentration. , Zhang et al reported that 1-(furan-2-yl)-2-hydroxyethan-1-one could be obtained from furfural (50 g/L) and formaldehyde through increasing the solubility of PDC from Sulfobacillus sp.…”
Section: Introductionmentioning
confidence: 99%